Evaluation of different fungicides against rice seedling rot incited by Sclerotium rolfsii Sacc. - Nath, Kedar; Patel, VP (ORYZA-An International Journal of Rice, 2023)
Seedling rot disease in rice incited by Sclerotium rolfsii Sacc. in the rice nursery raised during December to January for summer rice cultivation is an emerging threat to rice cultivation in South Gujarat. In the present climate change scenario, rice crop is facing the challenges of new diseases which were otherwise not touching the economical threshold. Eight fungicides were evaluated under in vitro condition. Tebuconazole 50% + trifloxystrobin 25%, mancozeb 63%+ carbendazim 12%, azoxystrobin 18.2%+difenoconazole 11.4%SC, azoxystrobin 11.5% + mancozeb 30.0% and thiram 75 WS gave complete mycelial growth inhibition at 50 ppm concentration. Whereas azoxystrobin 23SC and tebuconazole 2% DS showed good mycelial growth inhibition ability with 83.30 and 90.74%, respectively. Most effective fungicides under in vitro were evaluated against seedling rot disease under field conditions during 2018 to 2020. Seed treatment with fungicides revealed that rice seeds treated with azoxystrobin 23SC @ 1ml /kg seed and soil application with Trichoderma harzianum (2×106 cfu/g) @ 1 g/m2 which was at par with seeds treated with azoxystrobin 23SC @ 1ml/kg seeds and azoxystrobin 18.2% + difenoconazole 11.4 %SC @ 1ml/kg seeds effectively managed seedling rot disease and given highest plant population with minimum seedling mortality, improved shoot and root length and good seedling vigor index.